Pemberdayaan Komunitas RT Puri Cirebon Lestari melalui Pelatihan Kerajinan Decoupage dan Market Access - Maya Dewi Kurnia; Dina Pratiwi Dwi Santi; Setiyani Setiyani; Ena Suhena Praja (Jurnal Surya Masyarakat, 2021)
Housewives (RT) in one of the Talun Districts are active in activities every month, namely “arisan”. Unfortunately, those who are members of the RT Community just fill their spare time because on average they don't work in the formal sector. They want to increase their potential by not forgetting their obligations as wives or mothers at home. This is urgent to do to increase the potential of women in order to produce superior resources. Currently, women's participation in the business sector is increasing. This is due to the provision of equal and fair opportunities for women to carry out business activities, so that it is expected to help improve the family economy. Thus, it cannot be denied that women can strengthen the economic resilience of families and communities. Therefore, the team seeks to take advantage of opportunities to increase the potential of mothers by providing appropriate skills, raw materials that are easily available and having economic values. This skill is the decoupage. Method used to carry out community service in the form of lectures, questions and answers, and practice through four stages starting from the analysis process to determining the target output. The results obtained by partners are very enthusiastic and have a desire to practice independently to be more skilled. In addition, the participants had mastered the knowledge of techniques for making decoupage crafts and marketing.